Analysis of the Efficacy and Safety of Endoscopic Retrograde Cholangiopancreatography in Children With Symptomatic Pancreas Divisum - Pan, Guixian; Yang, Kaihua; Gong, Biao; Deng, Zhaohui (Frontiers in Pediatrics, 2021)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) has been increasingly performed in children with symptomatic pancreas divisum (PD). Aim: To investigate the safety and efficacy of ERCP in the treatment of children with symptomatic PD. Methods: We performed a retrospective analysis on children with PD who were treated with ERCP at Shanghai Children's Medical Center between June 2015 and May 2020. Pertinent patient, clinical and procedural data were collected to assess the therapeutic effects and identify the risk factors for post-ERCP pancreatitis (PEP). Results: Overall, 114 ERCPs were performed in 46 children with PD. With a median follow-up of 28.5 months (12–71 months), 40 (87.0%) children achieved clinical remission, the median number of acute pancreatitis episodes decreased from four times per year pre-operatively to once per year post-operatively (P < 0.001), and the nutritional score improved post-operatively (P = 0.004). The incidence of PEP was 7.9%, and female sex, stone extraction, and gene mutations were identified as possible risk factors for PEP on univariate analysis. However, there was no statistical significance on multivariate analysis (P > 0.05). Conclusion: Therapeutic ERCP is an effective and safe intervention for children with symptomatic PD.